Cooperative Operation Optimization for Port Groups Based on China's Practice - Lu, Bo. (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book focuses on port collaborative operation, an important emerging topic in the port and shipping industry, and deeply analyzes the high-quality collaborative mechanism of port groups from the perspectives of port groups' supply chain cooperative operation mechanism, port groups' logistics network optimization, port groups' collaborative scheduling optimization of resources, etc. Based on the combination of qualitative and quantitative analysis on China's cases, this book makes comprehensive use of game theory, network optimization, multi-dimensional resource cooperative scheduling optimization, and other theories and methods, and promotes the update and innovation of current research methods in related research areas. The feasible policy insights for optimization of port groups' collaborative operation are suggested at the end of book, which will help with the improvement of economic, environmental, and social benefits of port groups, and promote the port industry's innovation, upgrading, and transformation. The translation was done with the help of artificial intelligence. A subsequent human revision was done primarily in terms of content. The present version has been revised technically and linguistically by the authors in collaboration with a professional translator.
Chapter 1. Background of regional port groups cooperative operation -- Chapter 2. Synergy mechanism of port groups supply chain based on profit distribution -- Chapter 3. Logistics network optimisation of port groups -- Chapter 4. Operation optimisation of port group facilities and equipment resources -- Chapter 5. Resource integration and optimisation of port groups information system. Chapter 6. Effect evaluation of port groups integration and collaboration -- Chapter 7. Policy insights for port groups cooperative operation optimisation.
Keywords: Production management; Operations research; Operations Management; Operations Research and Decision Theory